Implementation Of The CLIS Model To Improve Student Learning Outcomes In Material Temperature And Changes - et. al., Dewi Diana Paramata, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to improve student learning outcomes on temperature and its changes by implementing the children learning in the science learning model. This type of research is a classroom action research model of Kemis and Taggart using two cycles: planning, implementing, observing, and reflecting. Students subject to action are class VIIB students of SMP Negeri 5 Gorontalo, the academic year 2019/2020, with several 30 people. The results showed that implementing the model of children learning in science could improve student learning outcomes; namely, in the first cycle, the percentage of learning completeness is still low and has increased in the second cycle. For the teacher activity, the total value of each aspect obtained is 76.7%. An increase in cycle II reached 83.4%, the aspect of student activity in cycle I was 9.67%, while in cycle II it increased by a percentage of 9, 81%, and student learning outcomes with an increase in the percentage of cycles I and II, from 66.6% to 96%. Based on this, it can be concluded that the implementation of the children learning in the science model can improve student learning outcomes.